KETIADAAN ILMU KALIGRAFI DALAM PEMBELAJARAN BAHASA ARAB - Arifa, Nabila (Jurnal Al-Hibru, 2026)
Calligraphy is an Islamic art whose spread has spread to various parts of the world, including in Indonesia. Several schools in Indonesia have made this calligraphy a mandatory learning curriculum. However, this calligraphy learning has challenges in teaching, including inadequate facilities, students' interest and motivation in learning. Calligraphy is closely related to learning Arabic, specifically writing skills (Maharah Kitabah), because with calligraphy learning Arabic can go interestingly, and students can express their ideas without hesitation about the mistakes that have occurred, since calligraphy is taught to be arranged according to the rules and has aesthetic value. This study uses a qualitative research method with a literature study approach by searching for data from journals that have been published in a certain period of time to find data that is relevant to the discussion of this article. The result found is that if this calligraphy is not taught, it will affect the learning of Arabic, especially the ability to write (Maharah Kitabah), including low writing skills, both in terms of neatness, aesthetics, and letterforms, and have an impact on errors in translating Arabic texts.